2015
DOI: 10.1186/s13039-015-0118-7
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variability in a Hungarian patient with the 4q21 microdeletion syndrome

Abstract: BackgroundInterstitial deletions of 4q21 (MIM 613509) have already been reported in more than a dozen patients with deletions ranging from 2 to 15.1 Mb delineating a common phenotype including marked growth restriction, hypotonia, severe developmental delay with absent or delayed speech and distinctive facial features. A minimal critical region of 1.37 Mb accounting for the common features with 5 known genes (PRKG2, RASGEF1B, HNRNPD, HNRPDL, and ENOPH1) has been described so far.ResultsHere we report on a 5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…At present, the biological functions of ENOPH1 are still mainly not known. It has been revealed in a few recent studies that there is wide expression of ENOPH1 in the brain and it is related to neurodevelopmental disorders, anxiety behavior and BBB function integrity damage (10,21,28). The present study was the first investigation of the role of ENOPH1 in the pathophysiology of gliomas.…”
Section: Discussionmentioning
confidence: 72%
“…At present, the biological functions of ENOPH1 are still mainly not known. It has been revealed in a few recent studies that there is wide expression of ENOPH1 in the brain and it is related to neurodevelopmental disorders, anxiety behavior and BBB function integrity damage (10,21,28). The present study was the first investigation of the role of ENOPH1 in the pathophysiology of gliomas.…”
Section: Discussionmentioning
confidence: 72%
“…Currently, the biological functions of ENOPH1 are largely unknown. A few recent studies have shown that ENOPH1 is widely expressed in the brain and is associated with neurodevelopmental disorders and anxiety (Barth et al, 2014 ; Komlósi et al, 2015 ). As the first study, here we investigated the role of ENOPH1 in ischemic stroke with a focus on the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…Severe growth retardation is a significant feature of 4q21 deletion syndrome. Previously, PRKG2 has been proposed as the candidate gene responsible for this phenotype [Komlosi et al, ]. Mutations in this gene cause dwarfism in beef cattle [Koltes et al, ], in rat [Chikuda et al, ; Tsuchida et al, ], and knockout mouse model [Pfeifer et al, ] but all in a recessive inheritance mode.…”
Section: Discussionmentioning
confidence: 99%
“…This is a non‐recurrent genomic disorder, presented with overlapping deletions of different size at 4q21 region. Currently, 48 cases (18 from literature [Bonnet et al, ; Dukes‐Rimsky et al, ; Tsang et al, ; Bhoj et al, ; Bartnik et al, ; Komlosi et al, ; Sakazume et al, ] and 30 cases from databases) with defined genomic coordinates have been reported and the majority of individuals with 4q21 deletion are characterized by neonatal hypotonia, intellectual disability, absent or delayed speech, marked progressive growth retardation, and variable degrees of brain malformation and facial dysmorphism.…”
Section: Introductionmentioning
confidence: 99%